Some Generalized Fixed Point Results with Applications to Dynamic Programming. (26th September 2020) - Al-Sulami, Hamed H.; Hussain, Nawab; Ahmad, Jamshaid
Abstract : The aim of this paper is to introduce some generalized contractions and prove certain new fixed point results for self-mappings satisfying these contractions in the setting of F -metric space. As an application of our results, we investigate the problem of dynamic programming related to the multistage process which formulates the problems of computer programming and mathematical optimization. We also provide an example to support the validity of our main results.